Characterization of magnetorheological brake utilizing synthesized and commercial fluids. (2021) - Acharya, Subash; Shyam Saini Tak, Radhe; Bhanu Singh, Surya; Kumar, Hemantha
Abstract: Magnetorheological (MR) brakes produce braking torque due to variation in the magnetorheological properties of the MR fluid when external magnetic field is applied. In this study, MR fluids having 70% and 80% weight fractions of iron powder were prepared and MR brake characteristics were tested for prepared MR fluids and a commercial Lord MRF 132 DG fluid. It was found that there was an increase in braking torque with applied current to MR brake at all speeds indicating the MR effect. With increase in weight fraction, there is an increase in braking torque though the reduction in speed is not significant. However, in case of MRF 132 DG fluid, the decrease in rpm is significant especially at higher speeds. Though, the prepared fluids and commercial fluid produce closer braking torque values at higher currents, the increase in braking torque without magnetic field to that with magnetic field at maximum current of MR brake utilizing commercial fluid is very high due to its low viscous torque. Finally, analysis in finite element method magnetics software combined with analytical equations was used to compute torque and compared with experimental results of MR brake utilizing commercial fluid.